Theatre brief - Cohen, Robert; Sherman, Donovan (McGraw-Hill Edication, 2020)
"You Be the Star in the Classroom Cohen and Sherman's Theatre Brief allows you to be the star in the classroom and puts students in the front row through an experiential approach. When students successfully master concepts with McGraw-Hill Education's LearnSmart and SmartBook, you spend more class time focusing on theatre as a performing art, fostering a greater appreciation for the course, and inspiring students to become life-long audience members. Mastering Concepts Cohen and Sherman's Theatre Brief offers an insider's guide to the world of theatre. Through the coverage of design, acting, and directing, students are given a behind-the-scenes look at professional theatre artists performing their craft. And, with LearnSmart/SmartBook, students are better able to understand and retain these important concepts"